The Effect Of Umkm Growth, Labor Force Participation Level And Kur On Grdp Of Lampung Province In The Period Of 2017-2021 - Nabila Choirunisa (Cita konsultindo, 2025)
GRDP is level development economy, and as inside reference assessment and planning development area. Research This aiming For know influence Growth of MSMEs, Labor Force Participation Rate, and KUR Against PDRB of Lampung Province Period 2017-2021. Methods in study This use method quantitative. The data used is secondary data, which is obtained from agency government whose data published in a way open on page officially. The data that I use taken through page official government namely Bps.go.id and bi.go.id. The data used is panel data in the form of annual data for the period 2017 to 2021 in 16 regencies /cities in Lampung Province. Data analysis uses panel data with a random effect regression model that is processed with Eviews 10. Based on results study state that The number of Micro, Small and Medium Enterprises (MSMEs) has an influence positive and significant to Product Gross Regional Domestic Product in Lampung Province 2017-2021. Labor Force Participation Rate has no effect significant to Product Gross Regional Domestic Product in Lampung Province 2017-2021. People's Business Credit has no effect significant to Product Gross Regional Domestic Product in Lampung Province 2017-2021.